Phase 1–2 study of vorinostat (SAHA), cladribine and rituximab (SCR) in relapsed B‐cell non‐Hodgkin lymphoma and previously untreated mantle cell lymphoma. (9th June 2019) - Spurgeon, Stephen E.; Sharma, Kamal; Claxton, David F.; Ehmann, Christopher; Pu, Jeffrey; Shimko, Sara; Stewart, August; Subbiah, Nan; Palmbach, Gundula; LeBlanc, Francis; Latour, Emile; Chen, YiYi; et al.
Summary: Altered DNA methylation and histone acetylation in lymphoma provided the rationale for using vorinostat (SAHA), cladribine and rituximab (SCR) in non‐Hodgkin lymphomas (NHL) in this phase 1–2 study (NCT00764517). Treatment included cladribine 5 mg/m 2 intravenously (IV) (days 1–5), rituximab 375 mg/m 2 IV (weekly 4× for cycle 1 and 1×/month) and vorinostat orally once daily (days 1–14) every 28 days for up to six cycles. Phase 1 included relapsed patients ( n  = 10) in a standard 3 + 3 dose escalation design (vorinostat: 200, 300 and 400 mg). No dose‐limiting toxicities were seen. The phase 2 dose for vorinostat was 400 mg po (days 1–14). The majority of phase 2 patients had mantle cell lymphoma (MCL) ( n  = 57; 39 previously untreated, 10 relapsed). The primary objective was objective response rate [complete response (CR) + partial response] which was 39% (7/18) in relapsed patients and 97% (38/39) with 80% (31/39) attaining a CR in previously untreated MCL. At a median follow‐up of 42 months, median progression‐free survival (PFS) and overall survival (OS) for relapsed NHL were 19·5 [95% confidence interval (CI): 2·0–33·0] and 25·0 (95% CI: 12·0–45·0) months respectively. Median PFS for previously untreated MCL was 84·0 months; OS could not be estimated. Toxicities were primarily haematological.